Direct steam reforming of diesel and diesel–biodiesel blends for distributed hydrogen generation. (5th January 2015) - Martin, Stefan; Kraaij, Gerard; Ascher, Torsten; Baltzopoulou, Penelope; Karagiannakis, George; Wails, David; Wörner, Antje
Abstract: Distributed hydrogen generation from liquid fuels has attracted increasing attention in the past years. Petroleum-derived fuels with already existing infrastructure benefit from high volumetric and gravimetric energy densities, making them an interesting option for cost competitive decentralized hydrogen production. In the present study, direct steam reforming of diesel and diesel blends (7 vol.% biodiesel) is investigated at various operating conditions using a proprietary precious metal catalyst. The experimental results show a detrimental effect of low catalyst inlet temperatures and high feed mass flow rates on catalyst activity. Moreover, tests with a desulfurized diesel– biodiesel blend indicate improved long-term performance of the precious metal catalyst. By using deeply desulfurized diesel (1.6 ppmw sulfur), applying a high catalyst inlet temperature (>800 °C), a high steam-to-carbon ratio ( S/C = 5) and a low feed mass flow per open area of catalyst (11 g/h cm 2 ), a stable product gas composition close to chemical equilibrium was achieved over 100 h on stream. Catalyst deactivation was not observed. Highlights: Suitable operating conditions for diesel steam reforming are determined. Stable product gas composition achieved over 100 h of on-stream exposure. Low catalyst inlet temperature and high feed flow rate induce catalyst deactivation. Liquid desulfurization (<2 ppmw sulfur) enhances long-term stability.